Pengabdian Kemitraan Masyarakat Aplikasi Penjualan Online Berbasis Web pada UMKM Kripik Aneka Rasa di Desa Padang Brahrang Kecamatan Selesai Kabupaten Langkat Provinsi Sumatera Utara - Gunawan, Gunawan; Yani, Achmad; Yusuf, Kadri; Sari, Marliana (Jurnal Masyarakat Indonesia (Jumas), 2025)
This community service aims to help UMKM with Variegated Flavors Chips in Padang Brahrang Village, Selesai District, Langkat Regency, North Sumatra Province. In this activity, assistance was provided in the form of the development of a web-based online sales application and the provision of 1 unit of Hewlet Packard laptop as an operational support facility. This program aims to increase the accessibility of marketing various flavored chips products and expand market reach through digital platforms. The methods applied include the design stage, application development, and application use training for MSME owners. The results of this activity show that this sales application helps MSMEs in managing products and transactions more effectively. In addition, the training conducted improves the ability of MSME owners to operate digital-based systems, so it is expected to have a positive impact on increasing sales and product competitiveness.